Retracted: Comparative analysis of distributive linear and nonlinear optimized spectrum sensing clustering techniques in cognitive radio network systems. Issue 5 (5th May 2021) - Babu R, Ganesh; Obaidat, Mohammad S.; V, Amudha; Manoharan, Rajesh; R, Sitharthan
Abstract: Retraction: "Comparative analysis of distributive linear and nonlinear optimized spectrum sensing clustering techniques in cognitive radio network systems" by authors Ganesh Babu R, Mohammad S. Obaidat, Amudha V, Rajesh Manoharan and Sitharthan R, IET Netw. 2021;1–11. https://doi.org/10.1049/ntw2.12027 . The above article, published online on 5 May 2021 in Wiley Online Library (wileyonlinelibrary.com ), has been retracted by agreement between the journal Editor‐in‐Chief, Han‐Chieh Chao and John Wiley and Sons Ltd . The retraction has been agreed due to evidence indicating that the peer review of this paper was compromised.